Effect of Medical-Grade Polyurethane Sponges on Sinus Membrane Perforation With a Lateral Window Approach - Hamada, Yusuke; AlSakr, Abudulaziz; Towns, Stephen; Blanchard, Steven B. (The Journal of oral implantology, 2021)
The most commonly reported complication during the sinus elevation surgical procedure is the perforation of the Schneiderian membrane. The aim of this retrospective study was to compare the rate of sinus membrane perforation during lateral window augmentation using either conventional sinus curettes or medical-grade polyurethane sponges. This retrospective study included patients who received a lateral window approach for sinus floor elevation. The sinus elevation procedures using medical-grade polyurethane sponges (test) or conventional curettes (control) were recorded and analyzed. All subjects' demographic data and preexisting conditions were evaluated. A total of 38 procedures met inclusion criteria, and those data were evaluated for analysis. There were no statistically significant differences in demographic data or preexisting conditions including age, sex, treatment location, presence and absence of septum, Schneiderian membrane thickness, and residual bone height between test and control groups. The membrane perforation rate was 7% in the test group and 43% in the control group; however, this difference did not reach statistical significance ( P = .064). Within the limitations of this study, although there was no statistically significant reduction of sinus membrane perforation with the use of medical-grade polyurethane sponges, the decreased incidence of perforation might be of clinical significance.